Effect of group impromptu music therapy on improving test anxiety and emotional regulation ability in medical students - Song, Li; Xiao, Rong; Wang, Changjing; Li, Chaoyang; Liu, Qi; Zhang, Ying; Liu, Zhen; Zhang, Lei; Zhang, Ming (Frontiers in Psychology, 2024)
IntroductionTest anxiety, a prevalent psychological issue among medical students, can profoundly impact their social, behavioral, and emotional development. This condition is significantly associated with challenges in emotional regulation, and to date, no effective clinical treatment has been established to address it. This study aimed to investigate the potential benefits and effects of group impromptu music therapy (GIMT) on enhancing emotional regulation skills and alleviating test anxiety in medical students.MethodsA total of 29 participants in the experimental group and 30 participants in the control group were finally included for data analysis. Four weeks prior to the final exams, the experimental group commenced GIMT treatment, while the control group did not receive any intervention. Following the four-week intervention period, both groups were assessed using standardized scales and follow-up semi-structured interviews.ResultsThe results revealed that students given the GIMT intervention reported significantly lower levels of test anxiety, as measured by the Test Anxiety Scale (TAS), and experienced fewer difficulties with emotional regulation, as indicated by the Difficulties in Emotion Regulation Scale (DERS). Additionally, these students achieved higher examination scores than the control group. Qualitative data from semi-structured interviews further supported these observations.DiscussionCollectively, these findings demonstrate that GIMT is an effective method for enhancing the emotional regulation abilities of medical students and for relieving the symptoms of test anxiety, ultimately resulting in better academic performance. The study also indicates that GIMT could be a promising clinical auxiliary method for dealing with test anxiety and should be considered for inclusion in the curriculum of healthcare professional education programs. Nonetheless, more efforts are needed to address the limitations of this method before it can be widely used for clinical practice.